2006
DOI: 10.1111/j.1365-2648.2006.03938.x
|View full text |Cite
|
Sign up to set email alerts
|

Using narrative pedagogy: learning and practising interpretive thinking

Abstract: By documenting students' experiences in courses in which Narrative Pedagogy is used, this study provides teachers with research-based evidence to guide their pedagogical decisions. It extends international efforts to develop discipline-specific pedagogies and offers a practical, student-centred approach teachers can use to enhance students' thinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 20 publications
0
70
0
Order By: Relevance
“…They also found that considering others' opinions expanded their thinking. Narrative pedagogy has been described in nursing education as one teaching strategy to increase students' abilities to challenge assumptions and interpret clinical findings, and think differently [39,40]. Similarly VTS helps students uncover meanings and serves as a path to help students discover their voice as they seek to find meaning in a work of art.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that considering others' opinions expanded their thinking. Narrative pedagogy has been described in nursing education as one teaching strategy to increase students' abilities to challenge assumptions and interpret clinical findings, and think differently [39,40]. Similarly VTS helps students uncover meanings and serves as a path to help students discover their voice as they seek to find meaning in a work of art.…”
Section: Discussionmentioning
confidence: 99%
“…9 Experiential learning, the main source of working or "how to" knowledge, 10 Narrative pedagogy, with its emphasis on how students learn and experience thinking, is also a befitting framework for DNP student course work, as they are encouraged to pool their wisdom, challenge their preconceptions, envision new possibilities and engage with others. [16][17] Student Video Productions…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…11,[13][14][15][16][17] Collectively, the frameworks propose learner engagement through ownership, active participation, idea testing, peer-review, and reflection related to content and learning process.…”
Section: Evaluation Phasementioning
confidence: 99%
“…Teachers who have critical thinking skills can better improve their students' critical thinking skills (Evans, 2008;Fullan, 2001). Therefore, teachers need to be models of critical thinking and to encourage students by sharing their knowledge, skills and beliefs (Herrenkohl & Wertsch, 1999;Ironside, 2006).…”
Section: Introductionmentioning
confidence: 99%